Analytical solutions of the microscopic two-band theory for the temperature dependence of the upper critical fields of pure MgB2 compared with experimental data - Palistrant, M.; Surdu, A.; Ursu, V.; Petrenko, P.; Sidorenko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Main theoretical results of the microscopic two-band theory for the temperature dependence of the upper critical fields Hc2(ab) and Hc2(c) in pure two-band systems like MgB2 are presented. The analytical solutions for the upper critical fields near the superconducting transition temperature and near the zero temperature were transformed to be directly compared with experimental data. The experimental Hc2(ab) and Hc2(c) temperature dependences of textured MgB2 films near the superconducting transition temperature were measured and compared with the respective theoretical formulas. The results of this theoretical approach were also compared with earlier published experimental data of other authors. The chosen method allows obtaining an accurate match between the theoretical expressions and experimental results.